Ecological connectivity of the Qiongzhou Strait: a case form Orangefin Ponyfish (Photopectoralis bindus) haplotype diversity and genetic structure - Xu, Lei; Zhang, Jinxia; Wang, Xuehui; Chen, Qinghua; Tang, Quehui; Wang, Lianggen; Ning, Jiajia; Li, Yafang; Liu, Shuangshuang; Huang, Delian; Du, Feiyan (Frontiers in Marine Science, 2024)
Grasping the genetic structure of marine fish populations is vital for comprehending species connectivity patterns and determining the appropriate spatiotemporal scales for conservation management strategies. Here, we analyzed the population genetics of the Orangefin Ponyfish (Photopectoralis bindus Valenciennes, 1835) by examining a portion of the gene coding for the mitochondrial cytochrome c oxidase subunit I. The aim was to evaluate the haplotype pattern, genetic structure, demographic history, as well as the influence of ecological connectivity through the Qiongzhou Strait on the distribution patterns of this species in the northern South China Sea and the Beibu Gulf.In total, 257 specimens yielded only 13 haplotypes, with the predominant haplotype present at all sampling locations. The analysis revealed a "star-like" haplotype pattern, indicating low levels of both haplotype and nucleotide diversity. Additionally, a small but significant genetic structure was observed between the coastal regions flanking the Leizhou Peninsula. These patterns in the haplotype network and genetic structure may be significantly influenced by contemporary currents, particularly through the connectivity of the Qiongzhou Strait. Tajima's D and Fu's Fs demonstrated pronouncedly negative values, along with a unimodal mismatch distribution, suggested a recent demographic expansion of Photopectoralis bindus during the late Pleistocene, likely influenced by fluctuations in sea levels.